The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1988
DOI: 10.1161/01.hyp.11.2_pt_2.i212
|View full text |Cite
|
Sign up to set email alerts
|

Atrial natriuretic factor in essential hypertension and adrenal disorders.

Abstract: AKIRA SUGAWARA, KAZUWA NAKAO, TSUYOSHI KONO, NARTTO MORD, TAKAYUKI YAMADA, HIROSHI ITOH, SHOZO SHIONO, YOSHIHIKO SATTO, MASASHI MUKOYAMA, HIROSHI ARAI, AND Hmoo IMURA SUMMARY Patients with untreated essential hypertension had significantly higher plasma atrial natriuretic factor (ANF) levels (92.9 ± 12.9 pg/ml, mean ± SE) than those of age-matched controls (37.8 ± 6.0 pg/ml; p<0.01). Plasma ANF levels in essential hypertensive patients showed a significant positive correlation with mean arterial pressure (MAP;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

1990
1990
2002
2002

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 22 publications
1
5
0
1
Order By: Relevance
“…ANP during salt loading and ∆ ANP were both significantly correlated with ∆ MBP in the total subjects and subjects 60 years ( p 0.0018-0.005), and ∆ ANP was a significant predictor of ∆ MBP by multiple regression analysis ( p 0.01). In agreement with a previous study (21), there was a significant inverse correlation between PRA and ANP in our study (r 0.35, p 0.002) (Fig. 3).…”
Section: Discussionsupporting
confidence: 94%
“…ANP during salt loading and ∆ ANP were both significantly correlated with ∆ MBP in the total subjects and subjects 60 years ( p 0.0018-0.005), and ∆ ANP was a significant predictor of ∆ MBP by multiple regression analysis ( p 0.01). In agreement with a previous study (21), there was a significant inverse correlation between PRA and ANP in our study (r 0.35, p 0.002) (Fig. 3).…”
Section: Discussionsupporting
confidence: 94%
“…Decreases of and the degree of pre-existing target organ damage of individual hypertensive patients determines the plasma ANP by atenolol and other beta-blockers, reported in a few patients, 40,42 may be explained if effects of treatment on plasma ANP. The multivariate model in our patients supports this view, and these agents improved severely impaired diastolic relaxation or controlled severe hypertension.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, neither PRA before treatment nor the renin status of the patients results could be explained on the basis of differ- ences in the pharmacologic profiles of individual in the rat. 44 Also, infusion of angiotensin II, at pressor 42 or subpressor 45 doses, increases plasma agents within the same family. However, this possibility has also been disproved by reports in which ANP in humans and dogs, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3) fur ther supports the notion that there is a reciprocal relation ship between the RAA system and ANP. Indeed, inverse relationships between PRA and ANP were previously reported in essential HT at rest [38,43], Ganau et al [38] and Sugawara et al [43] reported that plasma ANP levels were inversely related to PRA with coefficients of correla tion o f -0.40 and -0.43, respectively. Our findings of a weak inverse correlation between PRA and ANP (r value o f -0.41) were consistent with their findings.…”
Section: Neurohormonal Responses In Subgroups O F Hypertensives Basedmentioning
confidence: 80%